Little blue tractor: little stories collection - Baxter, Nicola; Goffe, Toni Briers, Richard (Ladybird Loughborough, 1997)
The Little Tractor looked out from the barn. On the farm everything was white and whirling. The snow didn't stop falling, and little Tractor decided he must bring the animals into the barn.